The Influence of Service Quality and Price Perception on Repurchase Intention at Salejourn Cafe and Space Padang - Rahmat Kurniadi Saputra; Khairani Saladin (Journal of Multidimensional Management, 2025)
The growth of the coffee shop industry in Indonesia has intensified competition, making customer retention essential for business sustainability. This study examines the influence of service quality and price perception on repurchase intention at Salejourn Cafe and Space Padang. A quantitative, causal–associative approach was applied, involving 130 purposively selected respondents aged at least 17 years who had visited the café within the last three months. Data were collected via a structured five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS version 26.0. The results show that both service quality (β = 0.145, p < 0.05) and price perception (β = 0.446, p < 0.05) significantly and positively affect repurchase intention, with price perception demonstrating a stronger impact. Together, these variables explain 78.7% of the variance in repurchase intention. The findings suggest that café managers should maintain high service standards while implementing competitive, value-driven pricing to enhance loyalty. Future research should consider additional factors such as brand image and promotional strategies.